Periods of the educational process and the technology of teaching based on them - Mukhtor Roziyev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article analyzes didactic phenomena in the field of the educational process - the activities of a teacher and a student during the formation of an act, phases, cycles, and stages of studying the material "Frage Sätze" in a German lesson in grade 5.